All in the name: the effect of elite source cues on value perception - Waheed, Moniza; Baumgartner, Susanne (Universiti Putra Malaysia Press, 2014)
This study investigated the effect of message source labeling (US politician versus Al-Qaeda leader) on citizens’ perception of their own values in comparison to their perception of values held by the message source. An experiment conducted on 145 participants found that citizens perceived the values of the political figure as more similar to their own when the political figure was labeled “US politician” instead of “Al-Qaeda leader”. However, when presented with a statement with no source labels, participants perceived the values of the US politician and the Al-Qaeda leader to be similar to one another.